Serratula coronata L. Mediated Synthesis of ZnO Nanoparticles and Their Application for the Removal of Alizarin Yellow R by Photocatalytic Degradation and Adsorption - Mashentseva, A.A.; Aimanova, N.A.; Parmanbek, N.; Temirgaziyev, B.S.; Barsbay, M.; Zdorovets, M.V. (Nanomaterials, 2022)
In this study, the potential of biogenic zinc oxide nanoparticles (ZnO NPs) in the removal of alizarin yellow R (AY) from aqueous solutions by photocatalytic degradation, as well as adsorption, was investigated. The synthesized ZnO NPs were prepared by the simple wet-combustion method using the plant extract of Serratula coronata L. as a reducing and stabilizing agent and characterized by powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy. Photocatalytic degradation of AY was monitored by UV–visible spectroscopy and the effects of parameters, such as light source type (UV-, visible- and sunlight), incubation time, pH, catalyst dosage and temperature on degradation were investigated. It was demonstrated that the source of light plays an important role in the efficiency of the reaction and the UV-assisted degradation of AY was the most effective, compared to the others. The degradation reaction of AY was found to follow the Langmuir-Hinshelwood mechanism and a pseudo-first-order kinetic model. The degradation kinetics of AY accelerated with increasing temperature, and the lowest activation energy (Ea) was calculated as 3.4 kJ/mol for the UV-light irradiation system, while the Ea values were 4.18 and 7.37 kJ/mol for visible light and sunlight, respectively. The dye removal by the adsorption process was also affected by several parameters, such as pH, sorbent amount and contact time. The data obtained in the kinetics study fit the pseudo-second-order equation best model and the rate constant was calculated as 0.001 g/mg min. The isotherm analysis indicated that the equilibrium data fit well with the Freundlich isotherm model. The maximum adsorption capacity of AY on biogenic ZnO NPs was 5.34 mg/g.
Keywords: biogenic nanoparticles; wet combustion synthesis; zinc oxide; alizarin yellow R; fotocatalysis; adsorption; dye removal; Serratula coronata L.